%VdotO2max as Physical Load Indicator Unit in Forest Work Operation - Efi Yuliati Yovi (Institut Pertanian Bogor (IPB University), 2007)
Most of forestry work has burdened forest workers with heavy workload, which is often exceeding their allowable workload. This workload has been widely measured through energy expenditure-based workload assessment (expressed in kcal/kg/min). However, this calculation method excluded physical characteristic of individual into its calculation, meanwhile it may greatly influenced metabolism system of an individual. Thus, there is a big possibility that the use of kcal/kg/min workload unit in comparing workload among different individuals conducting the same physical work had ended in an erroneous reading. Therefore, a study on alternative workload measurement that provides a fair assessment when the assessment is conducted among different individuals performing same physical activity is significantly important. This study proposed an alternative workload calculation approach, in which the workload unit was expressed in %VdotO2max. The results showed that alternative workload measurement provided excellent accurateness similar to that provided by conventional workload assessment method. Further analysis showed that the proposed unit showed a fair reading when the analysis was carried out to more than one individual. This was because the proposed unit considered maximum physical work capacity (short term) of each individual in its calculation.